SYNTHESIS OF SCHIFF-BASES BY CONDENSATION OF HETARYLCARBOXALDEHYDES WITH PARA-PHENETIDINE - KABAN, S; FIDANER, Z (SPRINGER WIEN, 1990)
Treatment of quinolinecarboxaldehydes and their derivatives with p-ethoxyaniline yields in a one-step reaction a series of new Schiff bases in 47-73% yield. The products [quinoline-2-, 6-methylquinoline-2-, quinoline-8-, and acridine-9N-(p-ethoxyphenyl)formimidoyl], have been fully characterized.
Keywords: Chemistry